Characterization of six IL-17 family genes in miiuy croaker and evolution analysis of vertebrate IL-17 family. (February 2016) - Yang, Qiong; Sun, Yuena; Su, Xiurong; Li, Taiwu; Xu, Tianjun
Abstract: Interleukin-17 (IL-17) family is a cytokine family which is one of the major signaling molecules family involved in immunity. Six member of IL-17 family cytokines (IL-17A-F) were found in mammals. In fish, all IL-17 family genes except IL-17B and IL-17E have been isolated and identified. Besides, IL-17N is uniquely found from teleosts. IL-17 family genes are widely studied in mammals, but have not been widely reported in lower vertebrates. In this study, we identify six IL-17 family genes (IL-17A/F1-3, IL-17C, IL-17D, IL-17N) from miiuy croaker, using LPS and poly (I:C) to infect miiuy croaker in order to analyze the expression response to bacteria and virus and expression in normal tissues. Challenge experiment showed that miiuy croaker IL-17 family genes exhibited more sensitive response to the poly (I:C) than the LPS. The expression of IL-17 in un-stimulated tissues showed that different gene has expressed in different tissues. Through the analysis of IL-17 family members exist in various representative species to study the evolution of the IL-17 family, and the result showed IL-17A/F, IL-17B, IL-17C, and IL-17D should be present in early gnathostomes species. Highlights: Six IL-17 family genes are identified in miiuy croaker. Miiuy croaker lacks IL-17B and IL-17E but possess IL-17N. Miiuy croaker IL-17 family genes exhibited more sensitive response to the Poly(I:C) than the LPS. We speculated about IL-17A/F, IL-17B, IL-17C, and IL-17D should be present in early gnathostomes species.